Effectiveness of Leaflet-Based Education for the Elderly on Knowledge of Covid-19 Prevention: Leaflet Education and COVID-19 Knowledge in the Elderly - Suardi, Suardi (Innovative Approaches in Health Science Journal, 2025)
Background: Covid-19 is an infectious disease caused by the acute respiratory syndrome coronavirus 2 (servere Acute Respiratory Syndrome Coronavirus 2 or SARS-coV-2). According to WHO, 2020 elderly people who are 80 years old are greatly affected by Covid 19 with a mortality rate reaching 21.9%. The purpose of the study was to see the effect of Leaflet-Based Education on the Elderly on Covid-19 Prevention Knowledge. Method: The method used is quasi experimental with a one-group pre-post tets approach. Research location in Takalar Regency, with a sample size of 32 elderly people. Data analysis used the Wilcoxon Signed Rank Test. Results: The results of the study, the average knowledge of Covid-19 prevention was 6.44. Meanwhile, after education the average knowledge of COVID-19 prevention was 11.53, meaning that the increase in knowledge after being given leaflet-based education was 5.09. From the analysis of the Wilcoxon Signed Rank Test, the value of ρ is 0.000 ≤ α (0.05). Conclusion: Conclusion on the effect of leaflet-based education on the elderly on knowledge of Covid-19 prevention in Takalar Regency.